2021
DOI: 10.1021/acs.jmedchem.1c00410
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Small GTPases and Their Prenylation in Diabetes Mellitus

Abstract: A fundamental role of pancreatic β-cells to maintain proper blood glucose level is controlled by the Ras superfamily of small GTPases that undergo post-translational modifications, including prenylation. This covalent attachment with either a farnesyl or a geranylgeranyl group controls their localization, activity, and protein–protein interactions. Small GTPases are critical in maintaining glucose homeostasis acting in the pancreas and metabolically active tissues such as skeletal muscles, liver, or adipocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 294 publications
0
25
0
Order By: Relevance
“…However, activated AMPK increased and thus GLUT4 expression did not significantly decreased in our study, which includes results from 20 different donors with individual variances being found. GLUT4 expression levels were confirmed at protein level by immunohistochemistry and Western blot in tissues from statin patients and in the statin-treated muscle cells [43,44].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, activated AMPK increased and thus GLUT4 expression did not significantly decreased in our study, which includes results from 20 different donors with individual variances being found. GLUT4 expression levels were confirmed at protein level by immunohistochemistry and Western blot in tissues from statin patients and in the statin-treated muscle cells [43,44].…”
Section: Discussionmentioning
confidence: 81%
“…In different cell types, such as adipocytes and ß-islet cells, statins are described to have a positive effect on insulin sensitivity and hyperglycemia. However, this is different for muscle, which may switch to an alternative pathway for GLUT4 translocation [43]. Statins inhibit the formation of isoprenoids and thus farnesyl and geranylgeranyl pyrophosphates, from the mevalonate pathway and required for small GTPase prenylation, are reduced [43,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoprenoids are produced by the mevalonate pathway, which is also involved in cholesterol biosynthesis. Some inhibitors of this route have been successfully used as therapeutic approaches for type 2 diabetes, given that Rab GTPases (including Rab1) are necessary for glucose homeostasis [ 218 ]. Statins, which are well-known blockers of cholesterol generation, are inhibitors of hydroxymethyl-3-methylglutaryl coenzyme A, a critical enzyme of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the CBS metabolic pathway, farnesyl diphosphate synthase (FDPS) is the key enzyme for isoprenoid biosynthesis, catalyzing isoprenylation of several small GTPases. 5 In this study, they found that inhibition of FDPS using zoledronic acid (Zol) sensitized pancreatic cancer cells to radiation and activated immune cells. 6 FDPS is overexpressed in PDAC tissue and cell lines and is associated with poor radiation therapy response and patient survival, making it a potentially suitable biomarker for radiation therapy response and an ideal target for developing PDAC therapy.…”
mentioning
confidence: 96%